Key Directions of Agricultural Export Development in Russian Regions - Olga G. Charykova; Marina E. Otinova; Aleksandr A. Tiutiunikov (Экономика региона, 2022)
Steady growth of global demand for agricultural products provides opportunities for Russian economic development. Since the country’s considerable (but geographically heterogeneous) agricultural potential and government policies encourage import substitution and food exports, the main possibilities for agricultural export development should be explored considering regional differences. The present research substantiates the feasibility of agricultural export development, assesses regional export potential and offers recommendations on export-oriented development of regional agri-food industries. Criteria-based assessment and cluster analysis methods were applied. The study database includes quantitative indicators of agriculture and agri-food trade dynamics observed in Russian regions. At the first stage, analysis and generalisation of relevant publications, world experience and current trends allowed us to substantiate the feasibility of export-oriented development of the Russian agricultural sector. At the second stage, in order to assess export orientation, export openness and international involvement of regional agri-food markets, a methodology was proposed and tested on the Central Black Earth region data. At the third stage, a cluster approach was created to classify Russian regions and examine the potential of agricultural production and foreign trade of the agri-food market. The research proposes recommendations on the development of agricultural and food exports for the most prospective regions. The presented approaches and findings can be used in strategies and programmes for monitoring the export-oriented development of regional agricultural sectors. Future research can focus on methodological design for assessing and modelling the development of regional agri-food markets.